Cell Impermeant-based Low-volume Resuscitation in Hemorrhagic Shock: A Biological Basis for Injury Involving Cell Swelling. Issue 3 (March 2016) - Parrish, Dan; Lindell, Susanne L.; Reichstetter, Heather; Aboutanos, Michel; Mangino, Martin J.
Abstract : Objective: To determine the role of cell swelling in severe hemorrhagic shock and resuscitation injury. Background: Circulatory shock induces the loss of energy-dependent volume control mechanisms. As water enters ischemic cells, they swell, die, and compress nearby vascular structures, which further aggravates ischemia by reducing local microcirculatory flow and oxygenation. Loading the interstitial space with cell impermeant molecules prevents water movement into the cell by passive biophysical osmotic effects, which prevents swelling injury and no-reflow. Methods: Adult rats were hemorrhaged to a pressure of 30 to 35 mm Hg, held there until the plasma lactate reached 10 mM, and given a low-volume resuscitation (LVR) (10%–20% blood volume) with saline or various cell impermeants (sorbitol, raffinose, trehalose, gluconate, and polyethylene glycol-20k (PEG-20k). When lactate again reached 10 mM after LVR, full resuscitation was started with crystalloid and red cells. One hour after full resuscitation, the rats were euthanized. Capillary blood flow was measured by the colored microsphere technique. Results: Impermeants prevented ischemia-induced cell swelling in liver tissue and dramatically improved LVR outcomes in shocked rats. Small cell impermeants and PEG-20k in LVR solutions increased tolerance to the low flow state by two and fivefold, respectively, normalized arterial pressure during LVR, and lowered plasma lactate after full resuscitation, relative to saline. This was accompanied by higher capillary blood flow with cell impermeants. Conclusions: Ischemia-induced lethal cell swelling during hemorrhagic shock is a key mediator of resuscitation injury, which can be prevented by cell impermeants in low-volume resuscitation solutions.